A Simple Synthesis of Polyfunctionalized 4‐Aminopyrazolidin‐3‐ones as 'Aza‐deoxa' Analogs of D‐Cycloserine. Issue 2 (February 2014) - Novak, Ana; Štefanič, Matej; Grošelj, Uroš; Hrast, Martina; Kasunič, Marta; Gobec, Stanislav; Stanovnik, Branko; Svete, Jurij
Abstract A simple five‐step synthesis of fully substituted (4RS, 5RS)‐4‐aminopyrazolidin‐3‐ones as analogs of D‐cycloserine was developed. It comprises a two‐step preparation of 5‐substituted (4RS, 5RS)‐4‐(benzyloxycarbonylamino)pyrazolidin‐3‐ones, reductive alkylation at N(1), alkylation of the amidic N(2) with alkyl halides, and simultaneous hydrogenolytic deprotection/reductive alkylation of the primary NH2 group. The synthesis enables an easy stepwise functionalization of the pyrazolidin‐3‐one core with only two types of common reagents, aldehydes (or ketones) and alkyl halides. The structures of products were elucidated by NMR spectroscopy and X‐ray diffraction.